2001
DOI: 10.1128/iai.69.5.2935-2942.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effective In Vitro Clearance ofPorphyromonas gingivalisby Fcα Receptor I (CD89) on Gingival Crevicular Neutrophils

Abstract: Porphyromonas gingivalis has been implicated as a causative pathogen in periodontitis. Immunotherapeutic approaches have recently been suggested to aid in the clearance of P. gingivalis from disease sites. Because antibody-Fc receptor (FcR) interactions play a role in the effector functions of polymorphonuclear neutrophils (PMN), we evaluated which FcR on PMN from gingival crevicular fluid (GCF) serves as an optimal target molecule for FcR-directed immunotherapy. GCF PMN and peripheral blood (PB) PMN from adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Other methods to reflect the activity of periodontal disease should be considered. We previously investigated the indicators of periodontitis activities in GCF that is in close contact with periodontal tissues 19‐21 . It is much better to determine the activity of periodontal disease using the GCF.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods to reflect the activity of periodontal disease should be considered. We previously investigated the indicators of periodontitis activities in GCF that is in close contact with periodontal tissues 19‐21 . It is much better to determine the activity of periodontal disease using the GCF.…”
Section: Discussionmentioning
confidence: 99%
“…25 Our recent study indicated the upregulation of phagocyte FcgRI expression to be observed in periodontal lesions. 26 Furthermore, injection of intravenous gamma globulin was found to induce FcgRIIb expression, leading to inhibition of phagocytic function mediated through activating FcgR. 27 Therefore, the 232I/ T allele may alter phagocytic activity in activating FcgRbearing phagocytes in the periodontal tissue or gingival crevicular fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Surface expression levels of FcγRIIa were analysed by flow cytometry (Kobayashi et al ., 2001). In short, purified mononuclear cells were incubated with Phycoerythrin (PE)‐conjugated anti‐CD14 monoclonal antibody (Becton Dickinson, San Jose, CA, USA) for 30 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%